The relationship between athlete burnout and perfectionism: A meta-analysis - Lainas, H.; Cho, S. (International Journal of Applied Sports Sciences, 2017)
In this meta-analysis, we examined the relationships between two types of perfectionism (i.e., perfectionistic strivings and concerns) and athlete burnout. A total of 18 studies in 17 articles (i.e., one article included two studies with different data sets) were included and analyzed. Random-effects models were used to test the relationships between perfectionism and burnout in athletes. The results indicated that perfectionistic strivings were negatively related to athlete burnout while perfectionistic concerns were shown to be positively related to athlete burnout. Perfectionistic strivings are functionally adaptive to burnout in athletes, whereas perfectionistic concerns are functionally maladaptive to athlete burnout. Gender significantly moderated the relationship between perfectionistic concerns and athlete burnout.